MENTAL WELL-BEING AMONG ADOLESCENTS WITH DIABETES DURING THE COVID-19 PANDEMIC - Cheng, Hooi Peng; Wong, Jeanne Sze Lyn; Selveindran, Nalini M; Amin, Noor Arliena Mat; Teoh, Sze Teik; Tee, Pian Pian; Gan, Cheng Guang; Anand, L Alexis; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION The COVID-19 pandemic has affected millions of lives worldwide causing great psychological stress. Adolescents with diabetes are particularly at risk of mental health issues during these unprecedented times. METHODOLOGY A cross-sectional study was conducted among adolescents with type 1 (T1DM) and type 2 diabetes mellitus (T2DM) age 10 to 18 years during the nationwide lockdown from June to December 2020 to assess the impact of COVID-19 on their mental health. We recruited and interviewed 87 participants regarding lifestyle changes, followed by the administration of Depression, Anxiety and Stress Scale (DASS-21). RESULTS There were 58 patients with T1DM (30 males, 51.7%) and 29 patients with T2DM (9 males, 31%) who participated in the study. Male gender, T2DM, puberty and presence of anxiety symptoms were associated with deterioration in glycaemic control post-lockdown. There was a deterioration in HbA1c among male and T2DM patients by 0.76% and 0.94% respectively (p=0.013 and 0.004, respectively). HbA1c increase pre- and post-lockdown was observed in patients with anxiety symptoms (9.39 ± 0.49 versus 10.16 ± 0.54%, p=0.028). Patients with stress symptoms showed improvement in their HbA1c (10.00 ± 0.57 versus 9.50 ± 0.063%, p=0.036). The incidence of depressive, anxiety and stress symptoms were detected in 34%, 41% and 26%, respectively in adolescents with no significant difference between T1DM and T2DM. Severe to extremely severe symptoms were seen for the subscale of depression (5.7%), anxiety (11.4%) and stress (6.9%). Lifestyle parameters (meal frequency, Physical Activity Questionnaire score, screen time and sleep duration) did not differ among the groups with or without the depressive, anxiety and stress symptoms. CONCLUSION There is a high prevalence of psychological disturbance among adolescents with diabetes during the pandemic. Anxiety was related to poor glycaemic control. Timely psychological assessment and support must be given to our young patients